Relationship Between Stressful Life Events and Sleep Quality: Rumination as a Mediator and Resilience as a Moderator - Li, Yukun; Gu, Simeng; Wang, Zhutao; Li, Hongfan; Xu, Xiayue; Zhu, Huan; Deng, Shiji; Ma, Xianjun; Feng, Guangkui; Wang, Fushun; Huang, Jason H. (Frontiers in Psychiatry, 2019)
Purpose: The aim of this study was to investigate the relationship between stressful life events and sleep quality, and probe the role of rumination and resilience in the relationship. Method: The Adolescent Self-Rating Life Events Checklist, Ruminative Responses Scale, Connor-Davidson Resilience Scale, and Pittsburgh Sleep Quality Index were used among 1065 college students. SPSS 20.0 and the SPSS macro PROCESS, which were specifically developed for assessing complex models including both mediators and moderators, were used to analyze the data. Results: High scores of stressful life events predicted worse sleep quality. Rumination partially mediated the relations between stressful life events and sleep quality. Resilience moderated the direct and indirect paths leading from stressful life events to sleep quality. Conclusions: The results demonstrate that stressful life events can directly affect the sleep quality of college students and indirectly through rumination. And increasing psychological resilience could decrease both the direct effect and the indirect effect of stressful life events affecting sleep quality. The results of this study may contribute to a better understanding of the effects, as well as the paths and conditions, of stressful life events on sleep quality in college students. Moreover, these findings can provide constructive suggestions for improving college students’ sleep quality.